2004
DOI: 10.1080/00207540412331281999
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing system engineering ontology for semantic interoperability across extended project teams

Abstract: Abstract:Communication, knowledge sharing and awareness of available expertise are complex issues for any multi-discipline team. Complexity increases substantially in extended enterprise environments. The concepts of an MSE moderator have previously been considered in environments with shared information models and vocabularies. These concepts are now translated to the realm of extended enterprises where inevitably individual partners will have their own terminology and information sources. An MSE ontology is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 19 publications
0
49
0
1
Order By: Relevance
“…They concluded that more attention should be paid to the problem of semantic interoperability even in a domain such as manufacturing environment where standardized solutions are usually anticipated. A manufacturing system engineering (MSE) ontology for semantic interoperability across extended project teams was reported in [19]. The MSE ontology enables the operation of an extended enterprise MSE Moderator to provide common understanding of manufacturing-related terms and therefore to enhance the semantic interoperability and reuse of knowledge resources within globally extended manufacturing teams.…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that more attention should be paid to the problem of semantic interoperability even in a domain such as manufacturing environment where standardized solutions are usually anticipated. A manufacturing system engineering (MSE) ontology for semantic interoperability across extended project teams was reported in [19]. The MSE ontology enables the operation of an extended enterprise MSE Moderator to provide common understanding of manufacturing-related terms and therefore to enhance the semantic interoperability and reuse of knowledge resources within globally extended manufacturing teams.…”
Section: Related Workmentioning
confidence: 99%
“…Communication and knowledge exchange between project teams comprising members from within information systems vendors, external consultants and different public organizations is often hampered by, among other things, confusion in terms and vocabulary [2]. Extended collaboration, such as joint private and public sector ventures, will raise the difficulty and complexity of communication between the cooperating stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Engineers working within a particular company or group will inevitably develop their own vocabulary, or common terms for particular issues, elements or activities and these will need to be adjusted to be more practical and to precisely meet the requirements of different projects or teams. Hence, when people are brought together from different groups or companies, two common types of problem can occur in communications that share and exchange information, firstly, that the same term is being applied to different concepts (semantic problem) and secondly, that different terms may be used to denote the same entity (syntax problem) [1].…”
Section: Introductionmentioning
confidence: 99%
“…This means that sufficient cross-understanding of each other's terminology is essential. An approach for doing this, based on a Manufacturing System Engineering (MSE) Ontology Model has been proposed in [1,6]. It has been designed to provide the explicit semantics of a common meta-model for a semantic and syntax interoperability service to enable cross-understanding of the basic manufacturing concepts, properties of concepts, relationships and constraints in concepts between different MSE applications.…”
Section: Introductionmentioning
confidence: 99%